The axiological assessment of projects into research ethics committees - Palma-Morgado, Daniel; Marín-Gil, Roberto; González-García, Lorena; Torelló-Iserte, Jaime; Santos-Lozano, José Manuel; Ortega-Calvo, Manuel (Ars Pharmaceutica (Internet), 2015)
The aim of this paper is to show that the existence of Ethics Research Committees is consistent with thehistorical time in which we reside. The idea of a neutral science dates back to the creation of the RoyalSociety. Putnam and other researchers proposed the term «epistemic values» to the values of science.This axiological transformation has been called in several ways: knowledge mode 2, post-normal science,post-academic science and technoscience. There is no innovation without evaluation, even withoutmultiple previous assessments. The actual existence of the Research Ethics Committees (RECs) is a factconsistent with the historical development of epistemology in the twentieth century. One of the mostimportant functions of RECs, is the axiological evaluation (epistemic values) of research projects.